Micromorphology and Thermostability of PEEK/PEI/PES Plastics Alloys - Chen, J.B.; Li, Z.Z.; Yang, X.H.; Qian, J.M. (Asian Journal of Chemistry, 2014)
PEEK/PEI/PES plastics alloys were prepared by twin-screw extrusion molding. Microstructure analysis showed that poly(ether imide) (PEI) and poly(aryl ether sulfone) (PES) can be well-balanced dispersed in poly(ether ether ketone) (PEEK) matrix. The PEEK has better compatibility with PEI than that of PES and that PEI can improve the compatibility between PEEK and PES and that there is a certain interaction between three components. But there are some regions in alloys without interaction between PEEK and PEI when PES was increased. Thermostability of materials could not be affected by alloying and there is little influence on the stability of ternary alloys for the heat treatment process of thermal compression molding.